Perbandingan Makna Kata “Tangan” pada Peribahasa Indonesia dan Mandarin - Nurvalentin, Nurvalentin; Karina, Karina; Andriani, Finna (Linguistik : Jurnal Bahasa dan Sastra, 2025)
This thesis is to show and to describe the similarity and difference of the meaning “Tangan” and “ ” between Mandarin and Indonesian language sentences. Using qualitative descriptive research method to describe and analysis the word between Mandarin and Indonesian languages. While research, using documentation technical to collect data in Mandarin and Indonesian both language. Primary data outcome from both language idiom dictionary and books contain those words. While obtaining and summerizing data that is quoted and written from the data in Indonesian and Mandarin, there are 8 types of pragmatic similar meanings in indonesian word “Tangan” and mandarin “ ? ”in two languages, such as brother sisters or family; doing things/job/to shop; to recieve or get; available or expertise in/good in; have a power to do. There are five meanings in indonesian but not available in mandarin, such as to describe me mysel; to take; income; to obey; to influence. There are 5 meanings also in Mandarin but not available in Indonesian, such as to describe easiness, to attack, chance, body and authority.